Evan Miller Is Waking Down - Law, Jerel (Thomas Nelson Incorporated, 2024)
What if dreams were dangerous? What if your strongest abilities made you a fugitive? Tweens and middle grade readers who enjoy dystopian and fantasy fiction will be pulled into a world of secrets, control, and power in this novel from Jerel Law, the author of the Jonah Stone: Son of Angels series. Cover – Title Page – Dedication – Copyright – Epigraph – Part 1. City 47 – Chapter 1 – Chapter 2 – Chapter 3 – Chapter 4 – Chapter 5 – Chapter 6 – Chapter 7 – Chapter 8 – Chapter 9 – Chapter 10 – Chapter 11 – Chapter 12 – Chapter 13 – Part 2. The Ruins – Chapter 14 – Chapter 15 – Chapter 16 – Chapter 17 – Chapter 18 – Chapter 19 – Chapter 20 – Chapter 21 – Chapter 22 – Chapter 23 – Chapter 24 – Chapter 25 – Part 3. Dreambender – Chapter 26 – Chapter 27 – Chapter 28 – Chapter 29 – Chapter 30 – Chapter 31 – Chapter 32 – Chapter 33 – Chapter 34 – Chapter 35 – Chapter 36 – Chapter 37 – Chapter 38 – Chapter 39 – Chapter 40 – Chapter 41 – Chapter 42 – Chapter 43 – Chapter 44 – Chapter 45 – Chapter 46 – About the Author. Fifteen-year-old Evan Miller's dreambending power takes him outside the limits of City 47, but when the Elders discover his nonconforming ability, he is forced to flee
Description based on publisher supplied metadata and other sources
Keywords: Conformity; Dreams; Ability; Fugitives from justice; Dystopias; Fantasy; Dystopian fiction; Fantasy fiction; Novels